2019
DOI: 10.1002/admt.201900064
|View full text |Cite
|
Sign up to set email alerts
|

Etching Techniques in 2D Materials

Abstract: 2D materials including graphene, transition metal dichalcogenides, and phosphorene have been widely researched for electronic and optoelectronic applications in recent years. Etching techniques for controlling the layer number and patterning shape of layered materials have been demonstrated to be a crucial part of the fabrication of various functional devices. Six types of etching techniques used in 2D materials are discussed, and the mechanism, purpose, and advantages of each technique are explored. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 137 publications
0
56
0
Order By: Relevance
“…[ 149 ] Based on the absence of covalent bonding between 2D materials and substrates, metal‐assisted splitting has been developed to eliminate etching‐induced contamination. [ 169,170 ] Specifically, 2D materials covered by a photoresist are defined by lithography and then deposited on a metal film, and a certain region of the 2D material defined by lithography is then peeled off to achieve patterning. As a lithography‐free technique, direct laser writing can locally heat and thin 2D materials without the use of masks, and precise control of laser movement and power allows one to realize diverse patterns with different numbers of layers.…”
Section: Synthesis Fabrication and Processing Of 2d Materials Beyonmentioning
confidence: 99%
“…[ 149 ] Based on the absence of covalent bonding between 2D materials and substrates, metal‐assisted splitting has been developed to eliminate etching‐induced contamination. [ 169,170 ] Specifically, 2D materials covered by a photoresist are defined by lithography and then deposited on a metal film, and a certain region of the 2D material defined by lithography is then peeled off to achieve patterning. As a lithography‐free technique, direct laser writing can locally heat and thin 2D materials without the use of masks, and precise control of laser movement and power allows one to realize diverse patterns with different numbers of layers.…”
Section: Synthesis Fabrication and Processing Of 2d Materials Beyonmentioning
confidence: 99%
“…So it's essential to control the layer number accurately. Several methods have been explored, such as layer etching, reactive gas etching, and metal-assisted splitting [86]. Das et al reported the controlled thickness of PdSe2 by SF6+N2 plasma, as shown in Fig.…”
Section: Large-scale Fabrication Of 2d Materialsmentioning
confidence: 99%
“…With the thickness decreasing from 9 layers to monolayer, the bandgap of WSe2 increases from 1.42 to 1.65 eV [149]. Because the thickness can be factitiously controlled, the layer-dependent bandgap makes it possible to design devices for a certain wavelength [86]. The layerdependent band structures affect not only photoresponse but also electronic transportation.…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…[24] Nanometer-sized pores were created in graphene by oxygen plasma or other plasmas. [25,26] Moreover, pores on the nanoscale were created in few-layered graphene using oxygen, ozone, or liquid phase etching using HNO 3 solution as etching reagents. [26][27][28] In addition, it is reported that a single Ni atom can be used to cut graphene to a nanomesh with a pore size of about 10-50 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Moreover, pores on the nanoscale were created in few-layered graphene using oxygen, ozone, or liquid phase etching using HNO 3 solution as etching reagents. [26][27][28] In addition, it is reported that a single Ni atom can be used to cut graphene to a nanomesh with a pore size of about 10-50 nm. [29] Sub-nanometer diameter pores in singlelayer graphene membranes were also fabricated, accordingly, defects were introduced into the graphene lattice through ion bombardment and oxidative etching enlarged defects into pores with sizes of 0.40 ± 0.24 nm.…”
Section: Introductionmentioning
confidence: 99%